O eu e a outra da colonização em Jane Eyre e Vasto mar de sargaços - Vieira, Luísa de Assis (2023)
This dissertation proposes the reading of the English novel Jane Eyre (1847) and the Caribbean novel Wide Sargasso Sea (1966), with the aim of tracing an analysis of the colonized female representation of the character Bertha Mason/Antoinette Cosway throughout the two works. We start from the analysis that the narration of the protagonist Jane reinforces the stereotype of the colonized woman and corroborates for the reader to build the image of a crazy, violent and dehumanized Bertha. On the other hand, the Dominican writer Jean Rhys constructs a novel whose central narrative is made by the voice of Bertha/Antoinette, so that the immigrant guarantees her space of speech and can tell what was confined in the attic of Thornfield Hall. The methodology used to carry out the work was comparative literature. To support the proposed analysis, the text addresses scientific productions on the subject, namely: Gabriela Souza Pinto (2017); Danielle Marques (2010); Ana Maria Zukoski, and Wilma dos Santos Coqueiro (2017). It also makes use of theoretical-critical productions and studies on identity, colonialism and postcolonial studies, such as Portrait of the Colonized Preceded by the Portrait of the Colonizer (MEMMI, 2007); The Madwoman in the Attic: The Woman Writer and the NineteenthCentury Literary Imagination (GILBERT & GUBAR, 2000); and The Empire Writes Back: Theory and practice in postcolonial literatures (ASHCROFT et al., 2002). Ultimately, we present arguments that Jane Eyre's narration dehumanizes Bertha, and that in Vast Sea of Sargassos, Antoinette tells the reader what lies behind Bertha Mason's dehumanization.